Architecture in the Emirates : AE - Jodidio, Philip (Hong Kong ; Los Angeles : Taschen, 2007)
Highlighting architectural trends by country, this series celebrates the richly hued architectural personality of each nation or region featured. Each book features 15 to 20 architects - from the firmly established to the up-and-coming - with the focus on how they have contributed to architecture in the chosen nation.
Aedas -- Tadao Ando -- Asymptote -- Atkins -- Behnisch Architects -- Frank O. Gehry -- Gensler -- Zaha Hadid -- Hok Sport -- Kazuhiro Kojima + Kazuko Akamatsu / C + A -- KPF -- Jean Nouvel -- OMA / Rem Koolhaas -- ONL -- Carlos Ott -- I.M. Pei -- RNL -- Hadi Simaan -- Skidmore, Owings & Merrill -- Various architects / Guggenheim Pavilions.
engineering bookfair2015
Text in English, French and German.
Keywords: Architecture -- United Arab Emirates -- History -- 20th century; Architecture -- United Arab Emirates -- History -- 21st century